PENGARUH PENEMPATAN KERJATERHADAP KINERJA KARYAWAN (STUDY PADA KARYAWAN DI PT. SIGNIFY COMMERCIAL INDONESIA ) - Prihatina Jati; Nursamsi Latif (Sekolah Tinggi Manajemen IMMI, 2020)
This study aims to determine the effect of placement on the performance of employees of cooperative employees ofPT. Signify CommercialIndonesia. This analysis uses the independent variable, namely placement, and the dependent variable is employee performance.. From the calculation of the correlation coefficient obtained is 0.674 and the results obtained from these calculations have a strong correlation level interpretation. This is because r = 0.674 which lies between 0.60 - 0.799 which means it has a strong correlation.. The results of this study prove that the hypothesis proposed is partially accepted because it shows significant test results. This means that placement has a very significant effect on employee performance by 45.4% where 54.6% is influenced by other factors. From the hypothesis test, it is found that the tcount value is 6.316 which is greater than the t table which is 2.010. Conclusion Ha is accepted and Ho is rejected, which means there is a positive correlation of the Effect of Placement on Employee Performance at PT. Signify Commercial Indonesia.